Pembentukan Karakter Disiplin Siswa - Raikhan Raikhan (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
The purpose of research as follows: 1). To know the character of student discipline. 2). To know the formation of student discipline character.3). To know the methods and solutions encountered in the formation of student discipline character.The formation of character in this individual will be very useful in his life in the family, school, and community environment, whether it is in school and after graduating from the level of education that followed. Discipline in the broad sense that is a mirror of the life of the people of the nation and state. The meaning, from the description of the level of discipline of a nation can be imagined how high the low level of the nation's culture it has. This research is done by using qualitative approach, that is approach directed to background and individual holistically (whole). So in this case it should not isolate individuals or organizations into variables or hypotheses, but view them as part of a wholeness. The results of this study, that in the formation of student discipline character, which must be considered is habituation, exemplary, and discipline itself. But in this case, there are constraints and problems in realizing and shaping the character of discipline in the students, among the obstacles faced are incomplete infrastructures, student background and the application of character of discipline into the subjects